Determinants of Economic Growth and Labor Productivity in Indonesia - Wildhan Surya Putra; Budiasih (Economics Development Analysis Journal, 2024)
Economic growth and labor productivity are important things for a region. This research analyzes the influence of investment, technological change, health, and minimum wages on economic growth and labor productivity. The geographically weighted regression (GWR) model is used to analyze spatial data, which produces local parameter estimates for each point/location where the data is collected. It was found that investment significantly affects economic growth in 18 provinces in Indonesia. ICT has a significant effect on economic growth in 3 provinces, and education (PPT) has a significant impact on labor productivity in 23 provinces. Low quality of health significantly affects the economic decline in 2 provinces and the decline in labor productivity in 4 provinces. The provincial minimum wage variable (UMP) significantly increases labor productivity in 17 provinces. Overall, of the 34 provinces, economic growth was most influenced by significant investment in almost all provinces except for Sumatra Island and half of Java Island. Meanwhile, labor productivity is most influenced by education, which is significant in almost all provinces except in eastern Indonesia and half of Sumatra Island.